2020
DOI: 10.1007/978-3-030-61705-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Hyperparameter Estimation for Anomaly Detection

Abstract: The detection of anomalies, i.e. of those points found in a dataset but which do not seem to be generated by the underlying distribution, is crucial in machine learning. Their presence is likely to make model predictions not as accurate as we would like; thus, they should be identified before any model is built which, in turn, may require the optimal selection of the detector hyperparameters. However, the unsupervised nature of this problem makes that task not easy. In this work, we propose a new estimator com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In our study, we found that to build the UL models for outlier detection require values for the contamination parameter to effectively detect outliers within the dataset. This parameter denotes the proportion of outliers present in the dataset and is relevant for both supervised (Bella, Fernández, & Dorronsoro, 2020) and unsupervised (Z. Xu, Kakde, & Chaudhuri, 2019) models.…”
Section: Model Trainingmentioning
confidence: 99%
“…In our study, we found that to build the UL models for outlier detection require values for the contamination parameter to effectively detect outliers within the dataset. This parameter denotes the proportion of outliers present in the dataset and is relevant for both supervised (Bella, Fernández, & Dorronsoro, 2020) and unsupervised (Z. Xu, Kakde, & Chaudhuri, 2019) models.…”
Section: Model Trainingmentioning
confidence: 99%